Color Blindness Testing Using A Client-Server Based on The Ishihara Method - Yudhi Ardiyanto; Muhamad Yusvin Mustar (Journal of Electrical Technology UMY, 2020)
The Ishihara method is one way to detect whether or not someone suffers from color blindness. This method possesses several sets of plates or circle patterns containing various combinations of colored dots and sizes, forming numbers visible for people with normal eyes. A collection of several plates with the name Ishihara book is available in the market. However, the book has a weakness for being easily damaged or faded in color. Although there are some shortcomings, several researchers have developed applications to anticipate those weaknesses. Being unable to be used by several people at once and the test history has not been adequately archived, are several examples of shortcomings of existing applications. This study aims to create a client-server-based color blindness testing mobile application. The system can provide real-time test results, and detailed test history is presented. Another feature is the push notification menu that sends messages to all users. This application has been designed and implemented successfully. Thereby, it can be used for a color blindness test before conducting a medical examination.